A heuristic for the multi-level capacitated lot sizing problem with inventory constraints. Issue 4 (2nd October 2019) - Witt, Andreas
ABSTRACT: In this paper, we present a heuristic for the multi-level capacitated lot-sizing problem (MLCLSP) with inventory constraints. This problem reflects one of the most difficult lot-sizing problems and has a high practical relevance. After addressing a mathematical definition a heuristic from the literature is enhanced to provide a solution approach. The heuristic starts calculating a solution for the uncapacitated problem and then performs backward and forward moves of the lot sizes. The approach can be used to control the work in process represented by inventories. Computational results based on different test instances are described and analysed. An example illustrates the approach of the heuristic.